Pengaruh Organisasi Terhadap Kemampuan Public Speaking Mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia STKIP PGRI Sampang - Nashihun Amin; Asri Bariqoh; Hanik Supriatin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2025)
Public speaking is an essential skill for students to face both academic and professional challenges. One factor believed to enhance this ability is participation in student organizations. However, many students have not fully utilized organizations as a medium for self-development, particularly in public speaking. This study aims to analyze the influence of organizational involvement on public speaking skills, identify contributing factors, and examine organizational strategies to improve these skills. The research employed a quantitative survey method involving 69 students selected through purposive sampling. Data were collected using questionnaires, observation, documentation, and analyzed with SPSS version 25 through validity and reliability tests, classical assumption tests, and simple linear regression. The findings reveal that organizational participation significantly affects students’ public speaking skills (sig. 0.000; F = 79.214). The most influential factors include the level of participation, roles undertaken, types of activities, and the social environment within the organization. Effective organizational strategies consist of communication training, group discussions, leadership development, and assigning active roles in activities. These results confirm that student organizations serve as an effective platform for shaping and enhancing students’ public speaking skills.